Epidemiologi Kasus Malaria Terkonfirmasi Positif di Kabupaten Muna - Irma Irma; Yusuf Sabilu; Suhadi Suhadi; Kamrin Kamrin (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2023)
Malaria is one of the most common mosquito-borne infectious diseases in the world. Globally, deaths due to malaria infection reported in 2019 amounted to 405,000 deaths with a total number of sufferers of around 228 million cases. Although malaria cases have continued to decline in the last five years, including in Southeast Sulawesi Province, there are still regencies/cities in Southeast Sulawesi that have not been free from malaria. Therefore this disease continues to be a burden of pain. This study is a descriptive study using secondary data on positive confirmed malaria cases from the Southeast Sulawesi Provincial Health Office.This study aims to describe malaria cases in Muna Regency during the period from 2016 to 2020 based on epidemiological variables, namely people and time. The results showed that positive confirmed malaria cases in Muna Regency from 2016 to 2020 showed a significant decline. From the people variable, the majority 56.95% of positive confirmed malaria cases were men and only 43.05% were women. Meanwhile, based on the time in five years of observation, the highest prevalence of confirmed positive malaria occurred in 2016 and the lowest in 2020. Malaria prevention and control programs need to be carried out strictly to reduce morbidity and achieve malaria elimination programs in Muna RegencyKey words: Malaria, confirmed positive, people, time.